Public administration: purposes, procedures and people - Frumarová, Kateřina, 1976-; Melotíková, Petra, 1981-; Nakladatelství Leges (Prague : Leges, 2025)
The publication is the work of a Czechia-Ukrainian team of authors and focuses on contemporary public administration as one of the fundamental pillars of a democratic state governed by the rule of law. It focuses on three interconnected levels that together form truly „good“ public administration: its purpose and value base, the processes and procedures by which it is carried out, and the human factor, which remains key even in the era of digitization and automation. The authors of the individual chapters analyse public administration as a service to the public, the purpose of which is to protect public subjective rights, but also to promote the public interest and strengthen citizens‘ trust in the exercise of public power. Special attention is paid to the principles of legality, liability, transparency, and respect for fundamental rights, as well as institutional and procedural mechanisms for the control and protection of individuals in relation to acts of public administration.
Publikace představuje komplexní pohled na současnou veřejnou správu jako klíčový pilíř demokratického právního státu. Autoři analyzují veřejnou správu ve třech vzájemně propojených rovinách – její hodnotové ukotvení a účel, procesy a postupy jejího fungování a roli lidského faktoru v podmínkách digitalizace a automatizace. Důraz je kladen na principy legality, transparentnosti, odpovědnosti a ochrany základních práv, stejně jako na mechanismy kontroly a ochrany jednotlivce vůči výkonu veřejné moci. Publikace zdůrazňuje význam veřejné správy jako služby veřejnosti a nástroje posilování důvěry občanů ve státní instituce.
Obsahuje bibliografii a bibliografické odkazy
Keywords: veřejná správa; působnost veřejné správy; veřejné služby; digitální transformace; Česko; kolektivní monografie; public administration; public administration competence; public utilities; digital transformation; Czechia; collective monographs